1.Doprowadź do najprostszej postaci .

a) (2+a)² + (2-a)²-2²-a² =

b) (2x+4)² - 4x² - 16 =

c) 9x² - 25 + (3x-5)(3x+5) - 2x=

d) (7 - y)²+(y+7)²+1=


2.Doprowadź do najprostszej postaci.

a)5(2x-4)² - x² - 9 + (x-3)²

b)(2a-4b)² - 2a² - 4b² + 3(2a-b)(2a+b)+5=

c)(8x+3)(8x-3) + (6x+2)² - 4(2x+7)=

d)2x(x²-2x+5) - 4x²(x²-2x+5)+10x³=


3

Odpowiedzi

2009-11-28T13:02:00+01:00
1.Doprowadź do najprostszej postaci .

a) (2+a)² + (2-a)²-2²-a² = (2+a)²+ (2-a)²-(2+a)(2-a) =
=(2+a)²+ (2-a)[(2-a) -(2+a) ] =(2+a)²+ (2-a)[2-a -2 -a] =
= (2+a)²+ (2-a)[ -2a)]=
=(2+a)²+ (-2a)(2-a) =
= 4 +4a +a² -4a -2a² =
= -a² +4=
=4 -a² =
=(2-a)(2 +a)

b) (2x+4)² - 4x² - 16 = 4a² +16x +16 -4a² -16 =
= 16x

c) 9x² - 25 + (3x-5)(3x+5) - 2x= 9x² - 25 +9x²+15x -15x -25=
= 18x²-50

d) (7 - y)²+(y+7)²+1= 49 -14y +y² + y² +14y +49 +1 =
= 2y² +99


2.Doprowadź do najprostszej postaci.

a)5(2x-4)² - x² - 9 + (x-3)² =
= 5( 4x² -16x +16) -x² -9 + x² -6x +9 =
= 20x² -80x +80 -6x=
= 20x² -86x +80=
=2( 10x² - 43x +40)


b)(2a-4b)² - 2a² - 4b² + 3(2a-b)(2a+b)+5=
= 4a² -16ab +16b² -2a² -4b² +3(4a² -b²) +5 =
= 2a² -16ab +12b² +3(4a² -b²) +5 =
= 2a² -16ab +12b² + 12a² -3b² +5 =
= 14a² -16ab +9b² +5


c)(8x+3)(8x-3) + (6x+2)² - 4(2x+7)=

= 64x² -9 + 36x² +24x +4 -8x-28 =
= 100x²+16x -33


d)2x(x²-2x+5) - 4x²(x²-2x+5)+10x³=
= 4x³ -4x² +10x - 4x⁴ +8x³ -20x² + 10x³=
= -4x⁴+22x³ -24x² +10x



2 5 2
2009-11-28T13:12:36+01:00
1.
a) (2+a)² + (2-a)²-2²-a² = (2+a)(2+a)+(2-a)(2-a)-4-a²= 4 +2a + 2a + a² + 4 -2a -2a +a²-4-a²= 4+a²

b) (2x+4)² - 4x² - 16 =(2x+4)(2x+4) -4x² -16=4x² + 8x + 8x + 16 -4x² -16= 16x

c) 9x² - 25 + (3x-5)(3x+5) - 2x=9x² - 25 + (9x²+15x-15x-25)=9x² - 25 + 9x² -25=18x² -50

d) (7 - y)²+(y+7)²+1=(7 - y)(7 - y)+(y+7)(y+7)+1=49-7y-7y+y²+y²+7y+7y+49+1=99 + 2y²

2.

a)5(2x-4)² - x² - 9 + (x-3)²=5(2x-4)(2x-4) - x² +9 +(x-3)(x-3)= 5(4x² -8x -8x +16) -x² + 9 +x² -3x -3x +9=20x²-40x -40x + 80 - x² +9 +x² -3x -3x +9=20x² -86x +98

obecnie tyle mogę rozwiązać, gdyż nie mam czasu, sorry
1 5 1
Najlepsza Odpowiedź!
2009-11-28T13:12:43+01:00
A) (2+a)² + (2-a)²-2²-a² =
4+4a+a²+4-4a+a²-4-a²=
a²+4

b) (2x+4)² - 4x² - 16 =
4x²+16x+16-4x²-16=
16x

c) 9x² - 25 + (3x-5)(3x+5) - 2x=
9x²-25+9x²-25-2x=
18x²-50-2x

d) (7 - y)²+(y+7)²+1=
49-14y+y²+y²+14y+49+1=
99+2y²


2)
a)5(2x-4)² - x² - 9 + (x-3)²=
5(4x²-16x+16)-x²-9+x²-6x+9=
20x²-80x+80-x²-9+x²-6x+9=
20x²-86x+80

b)(2a-4b)² - 2a² - 4b² + 3(2a-b)(2a+b)+5=
4a²-16ab+16b²-2a²- 4b² +3(4a-b²)+5=
4a²-16ab+16b²-2a²- 4b² +12a²-3b²+5=
14a²+9b²-16ab+5

c)(8x+3)(8x-3) + (6x+2)² - 4(2x+7)=
64x²-9+36x²+24x+4-8x-28=
100x²+16x-33

d)2x(x²-2x+5) - 4x²(x²-2x+5)+10x³=
2x³-4x²+10x-4x⁴+8x²-20x²+10x³=
8x³-16x²+10x-4x⁴
1 5 1